2008
DOI: 10.2196/jmir.1118
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Medical Blogosphere: An Online Survey of Medical Bloggers

Abstract: Background Blogs are the major contributors to the large increase of new websites created each year. Most blogs allow readers to leave comments and, in this way, generate both conversation and encourage collaboration. Despite their popularity, however, little is known about blogs or their creators.Objectives To contribute to a better understanding of the medical blogosphere by investigating the characteristics of medical bloggers and their blogs, including bloggers’ Internet and blogging habits, their motivati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
76
1
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(85 citation statements)
references
References 5 publications
1
76
1
4
Order By: Relevance
“…A study of medical bloggers (Kovic et al 2008) noted that survey respondents' motivations for blogging were different from the generality of bloggers: "Sharing practical knowledge and skills, as well as influencing the way other people think, were major reasons for blogging among our medical bloggers, but not among general bloggers".…”
Section: The Slow Growth Of Science Bloggingmentioning
confidence: 98%
“…A study of medical bloggers (Kovic et al 2008) noted that survey respondents' motivations for blogging were different from the generality of bloggers: "Sharing practical knowledge and skills, as well as influencing the way other people think, were major reasons for blogging among our medical bloggers, but not among general bloggers".…”
Section: The Slow Growth Of Science Bloggingmentioning
confidence: 98%
“…Kovic, Lulic, and Brumini (2008) interviewed 197 bloggers for English-language medical blogs who had posted within the previous month. The study revealed that sharing practical knowledge and skills, as well as influencing the way other people think, were major reasons for blogging among the medical bloggers.…”
Section: Blogs and Their Usementioning
confidence: 99%
“…Several studies of the dissemination of health information online have examined peer-to-peer communication and information exchange via blogs and online discussion fora [22][23][24]. To our knowledge, however, this is the first study to assess the content and valence of health information disseminated by advocacy groups online.…”
Section: Discussionmentioning
confidence: 99%